LABORATÓRIO DE ENSINO DE MATEMÁTICA: METODOLOGIAS PARA UMA APRENDIZAGEM SIGNIFICATIVA - Reis, Ana Q. M.; Silva, Denise K. d.; Pozzobon, Marta C. C.; Bohrer, Graciela P. M. (Salão do Conhecimento, 2013)
Resumo